Thermal Analysis of Greenhouse Environment Using Computational Fluid Dynamics (CFD), Case Study in ITERA - Drantantiyas, Nike Dwi Grevika; Ramli, Asyarf Nur; Suaif, ahmad; Yehezkiel, Listra Ginting (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Greenhouse is a modern agricultural technology that allows for increased agricultural yields. The purpose of this study was to analyze the thermal distribution in the greenhouse of the Sumatra Institute of Technology (ITERA) in 3 time conditions, namely in the morning, afternoon and evening. The method used is CFD modeling using Solidwork. The dimensions of the greenhouse are 12.5 x 25 x 4.26 m³. The greenhouse is divided into a grid into 20 thermal measurement points separated by 2.5 m. The greenhouse has 2 cooling pads and 2 exhaust fans separated by 12.5 m. Model validation using MAPE and R2. The results of the analysis show that 3 models have valid results with MAPE 10% and R2 0.75 and can continue in the review of thermal distribution. of the 3 time condition models that provide a thermal distribution of 28 - 37 ℃. Morning conditions are hotter than afternoon and evening. Cold air from the cooling pad sucked by the exhaust fan is only able to control an area 50%. So the thermal distribution of the greenhouse needs improvement.